Diabetes Treatment Satisfaction on Hospital Outcome through Patient Empowerment - Tjiptabudi, Vitta; Antonio, Ferdi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
This study examines the relationship between Patient Satisfaction with Diabetes Treatment and Hospital Reputation, with Patient Empowerment and Well-being acting as mediators. Additionally, this study includes Lifestyle as the moderating component. This quantitative, cross-sectional study employs a survey methodology using a structured questionnaire of respondents selected by quota sampling. A total of 160 respondents were obtained from two private hospitals. Data was analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). Diabetes Treatment Satisfaction is assessed as a higher-order construct (HOC) consisting of dimensions of Patient Empowerment as a lower-order construct (LOC). The three LOCs are Patient Control, Patient Participation, and Patient Support. This study employs a disjoint two-step methodology. The research findings indicate a strong and positive relationship between Diabetes Treatment Satisfaction and Hospital Reputation mediated by Patient Empowerment and Patient well-being. The indirect effect is statistically significant (p-value < 0.05, CI 95%). The analysis also reveals a strong relation between Patient Well Being and Hospital Reputation (β=0.842, f2=2.427). However, the Lifestyle variable did not substantially relate to the relationship between Diabetes Treatment Satisfaction and Patient well-being. This study model has been empirically validated to provide sufficient explanatory and predictive capacities for assessing hospital reputation.